Improving cardiorespiratory fitness and quality of life among heart failure patients: A comparative study of circuit resistance training and myofascial release techniques. - Sergio R Thomaz; Cássia Da Luz Goulart; Natália Turri-Silva; Felipe A Teixeira; Luis Freitas; Glauco Lima Rodrigues; Graziella França B Cipriano; Gerson Cipriano; Lawrence P Cahalin (PLoS ONE)
Background Heart failure (HF) imposes limitations due to severe dyspnea and fatigue, which are often linked to diminished exercise tolerance, potentially influenced by compromised microvascular density, blood flow, and muscle strength. Myofascial release techniques (MRT) have demonstrated the capacity to enhance blood flow by reducing fascial tension. Purpose To assess the impact of incorporating MRT into Circuit Resistance Training (CRT) in comparison to an unsupervised home-based rehabilitation (RUHB) program on exercise tolerance (ET), muscle strength (MS), quality of life (QoL), and depression in patients with HF. Methods A randomized clinical trial involved HF patients with reduced ejection fraction (HFrEF, ejection fraction <50%) and NYHA classes II-IV. Participants were randomly assigned to either CRT (performing 2 circuits of 8 exercises thrice a week for three months) or CRT+MRT (receiving a combination of CRT and 6 MRT interventions once a week). Assessments included cardiopulmonary exercise tests (CPET) to measure ET, MS evaluated through One Repetition Maximum (1RM), QoL using the Minnesota Living with HF Questionnaire (MLwHFQ), and Depression through the Beck Depression Inventory (BDI) conducted before and after the interventions. Results Thirty-eight patients (14 in CRT, 14 in CRT+MRT, and 10 in RUHB), with a mean age of 55 years and 50% male, completed the study. After 12 weeks, only the CRT group displayed a significant effect in certain ET variables VO2 peak [baseline 12 (9-15) vs post 16 (11-19) ml/kg/min, p<0.05], VO2peak (ml/min) [baseline 848 (640-1056) vs post 1103 (852-1355) p<0.05], VE/VCO2 slope [baseline 34 (27-41) vs post 31 (27-36) p<0.05] and VO2/HRpeak [baseline 7 (5-9) vs post 11 (8-14) p<0.05]. There were significant decreases in the ΔMLwHFQ in the CRT group vs. RUHB (p<0.001) and CRT+MRT group vs. RUHB (p<0.001), demonstrating improved quality of life after 12 weeks in CRT and CRT+MRT groups. Conclusion Our findings suggest that CRT alone is sufficient to enhance cardiorespiratory function and muscle capacity, improve the quality of life, and alleviate depression in individuals with HF.